2000
DOI: 10.1046/j.1439-0310.2000.00611.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes In Rhesus Macaque ‘Coo’ Vocalizations during Early Development

Abstract: In order to test whether ‘coo’ calls of young rhesus macaques, Macaca mulatta, undergo some modifications during early development, and to explore which factors may influence these changes, we studied the ontogeny of their contact call, the ‘coo’ call. Vocalizations were recorded during brief periods of social separation. Infants were either raised with their mothers and other conspecifics, or separated from their mothers at birth and housed in a nursery with other infants. We recorded calls uttered in the sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
1
6

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 94 publications
(87 citation statements)
references
References 28 publications
3
74
1
6
Order By: Relevance
“…Area 23, comprising the caudal portion of the cingulate gyrus and cytoarchitectonically distinct in having granularity and layering, was unresponsive to electrical stimulation. The 'cooing sounds' mentioned in this paper are likely acoustically similar to the cry sounds of rhesus infants (see [32] for a detailed acoustic analysis), hence Smith's study represents perhaps the first indication that the anterior cingulate region is part of the cry circuit, at least in nonhuman primates. In an extensive study involving lightly anesthetized monkeys (macaques and guenons), cats and dogs, Kaada [44] found that vocalizations could be evoked in about half of the monkeys (but none of the cats or dogs) by stimulating the anterior ends of the limbic and hippocampal gyri.…”
Section: Forebrain Mechanisms Of Cry Productionmentioning
confidence: 63%
“…Area 23, comprising the caudal portion of the cingulate gyrus and cytoarchitectonically distinct in having granularity and layering, was unresponsive to electrical stimulation. The 'cooing sounds' mentioned in this paper are likely acoustically similar to the cry sounds of rhesus infants (see [32] for a detailed acoustic analysis), hence Smith's study represents perhaps the first indication that the anterior cingulate region is part of the cry circuit, at least in nonhuman primates. In an extensive study involving lightly anesthetized monkeys (macaques and guenons), cats and dogs, Kaada [44] found that vocalizations could be evoked in about half of the monkeys (but none of the cats or dogs) by stimulating the anterior ends of the limbic and hippocampal gyri.…”
Section: Forebrain Mechanisms Of Cry Productionmentioning
confidence: 63%
“…The calls of young meerkats were higher pitched than those of adults, similar to infant primates (e.g., Seyfarth and Cheney 1986;Gouzoules and Gouzoules 1989;Hammerschmidt et al 1994Hammerschmidt et al , 2000, young rodents (Blumstein and Munos 2005;Randall et al 2005), and human children (Scheiner et al 2002). Changes in fundamental and peak frequency-related parameters determining the pitch are likely to reflect physical maturation because of the increasing length of the vocal tract and the size of the resonance cavities as individuals age and grow (Fitch and Hauser 1995;Fischer et al 2002).…”
Section: Discussionmentioning
confidence: 91%
“…olfactory [34], visual [35,36]), acoustical studies on kin discrimination are more common [37][38][39]. Vocal communication is especially important among primates as it may provide various types of information about the vocalizer, such as identity [40], sex [41] , age [42], size [43], hormonal state [44,45] and very likely kinship [37,39,46,47]. The acoustic structure of 'coo' calls, a contact call uttered in pro-social context, in rhesus macaques suggest that it encodes information about maternal kinship [46].…”
Section: Introductionmentioning
confidence: 99%